More-than-human - Jaque, Andrš, 1971-; Otero Verzier, Marina; Pietroiusti, Lucia; Mazza, Lisa (Het Nieuwe Instituut ; Serpentine Galleries : Office for Political Innovation ; Manifesta Foundation, 2020)
The 'More-than-Human' reader brings together texts by writers across a wide array of disciplines that reflect on the state of post-anthropocentric thinking today. Focusing on the ecologies and technologies of climate injustice and inequalities, as well as the destructive structures lurking within anthropocentrism, More-than-Human proposes complex entanglements, frictions, and reparative attention across species and beings. Thinking past the centrality of the human subject, the texts that compose this reader begin to imagine networks of ethics and responsibility emerging not from the ideologies of old, but from the messy and complex liveliness around us, and underfoot.